Comparison of Life Quality between Diabetic and Diabetic with Tuberculosis Patients - Widuri Wita Andriati Shariefuddin; Sri Yusnita Irda Sari; Tri Damiati Pandji (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: There are increasing double burden disease in the world. One of the double burden problems is diabetes mellitus (DM) and Tuberculosis (TB). DM is a metabolic disease while TB is an infectious disease. The increasing number of people with DM and TB will affect the relationship between the two diseases (DM-TB). DM is an incurable disease that if it is not controlled properly will affect the person’s quality of life. This study was conducted to determine the quality of life (QoL) in people with diabetes compared to diabetic patients who also suffer from tuberculosis at Dr. Hasan Sadikin General Hospital, Bandung.Methods: This was a cross sectional study which included fifty three respondents in each DM and DM-TB group using the consecutive samplingmethod. The World Health Organization Quality of Life (WHOQoL-BREF) questionnaire was given after written informed consent was obtained from respondents. This study was conducted from April to November 2014 at the Endocrine and metabolism policlinic in Dr.Hasan Sadikin General Hospital.Results: The result showed that the total QoL score of DM patients was 58.8, DM-TB patients was 53.59 which was significantly different between the two groups (p=0.004). Out of four domains, physical (p=0.008), psychological (p=0.008) and environmental health (p=0.001) were significantly different between the two groups. There was no significant difference in social relationships domain (p=0.771).Conclusions: Lower QoL among DM-TB patients indicates that improvement in education or counseling particularly about physical, psychological and environment changes is recommended. [AMJ.2016;3(3):440–5]DOI: 10.15850/amj.v3n3.891